The impact of obesity on clinical outcomes in acute pancreatitis: a systematic review - Kosztyła-Czech, Zofia; Kowalska, Marta; Mazur, Anna; Brodziak, Julia; Fojcik, Katarzyna; Ciszewska, Wiktoria; Wiśniewski, Tomasz; Dworak, Michał; Werenkowicz, Wiktor; Matyja, Mateusz (Quality in Sport, 2026)
Background: Obesity may influence the severity of acute pancreatitis (AP) by intensifying inflammatory and metabolic disturbances. However, evidence is inconsistent due to differences in patient characteristics and AP causes. Clarification is needed to determine if obesity reliably predicts severe AP and complications. Aim:To evaluate the association between obesity, disease severity, complications, and clinical outcomes in AP. Methods: We conducted a systematic review of observational studies following PRISMA guidelines. We searched databases for studies on adult AP patients assessing obesity or BMI in relation to disease severity, organ failure, local complications, ICU admission, or mortality. We excluded studies on visceral adiposity indices only, pediatric cohorts, non-original publications, and non-RCT/non-observational designs. Results: Eleven studies met the inclusion criteria. Most reported that obesity is linked with increased AP severity and higher rates of systemic or local complications, such as organ failure, necrosis, and greater healthcare utilization. Large database studies confirmed increased complication rates in obese patients. However, findings regarding mortality were inconsistent: some studies noted higher mortality in overweight individuals, others showed no difference. Studies using BMI as a continuous variable found a consistent association between higher BMI and increased AP severity. Conclusions: Obesity appears to be associated with more severe AP and selected complications, but its link to mortality remains unclear. BMI alone shows limited predictive value and should be interpreted alongside other clinical data. Further research is required to standardize the incorporation of obesity into early AP risk assessment.